The Comparison of The Death Time of Hanged and Unhanged Broilers After Slaughter - Azhari Azhari; Sugito Sugito; Ferllya Adela Putri; Wahyu Eka Sari; M. Jalaluddin; Hamny Sofyan; Muttaqien Muttaqien; Rosmaidar Rosmaidar; M. Isa (Jurnal Medika Veterinaria, 2023)
Halal slaughter is a way to kill animals by the process of draining blood properly, perfectly, and according to the sharia. One of the critical points of halal in the slaughtering process is the timeof death of the broilers after slaughter. The objective of this study was to determine the difference between the time of death of hanged broilers and unhanged broilers, in order to find out the right time before the scalding. The samples used were 10 male broilers (Gallus domesticus) five weeks old with body weight 1.6-1.7 kg/head. The variable observed was the time of death of hangedand unhanged broilers after slaughter looking at the signs of  death,  such  as  heart  rate  stopped,  pupil or  eyelid  reflexes,  and  stopped breathing. This study used a completely randomized design (RAL) with two treatments, such as slaughter of chickens in a hanging position (P1) and chickens without hanging (P2). The test data were analyzed using the independent T-test SPSS 25. The results obtained that the average time of death of hanged broilers after slaughter was 82,80 seconds, while the average time of death of unhanged broilers was 162.60 seconds. The test results of the two treatments with a significant level of 0.05 showed a significant difference. The conclusion of this study was time of death of hanged broilers is faster than that of unhanged broilers after slaughter